2013
DOI: 10.1080/09593330.2013.829110
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ammonia removal at room temperature by pH controlled partial nitrification and subsequent anaerobic ammonium oxidation

Abstract: The Anammox based processes are suitable for the treatment of wastewaters characterized by a low carbon to nitrogen (C/N) ratio. The application of the Anammox process requires the availability of an effluent with a NO 2 --N/NH 4 + -N ratio composition around 1 g·g -1 , which involves the necessity of a previous step where the partial nitrification is performed. In this step the inhibition of the nitrite oxidizing bacteria (NOB) is crucial. In the present work a combined partial nitrification-Anammox two units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Durán et al [27] also observed that the FNA caused the suppression of NOB from a reactor where the partial nitritation took place at 20 ºC and 400 mg NH4 + -N/L. They based the operation of this system on the control of the NH4 + -N/IC ratio, which was maintained at values of approximately 0.82 g N/g C, close to the values used in the present study.…”
Section: Influence Of the Inlet Ammonium To Inorganic Carbon Ratio (Nsupporting
confidence: 84%
“…Durán et al [27] also observed that the FNA caused the suppression of NOB from a reactor where the partial nitritation took place at 20 ºC and 400 mg NH4 + -N/L. They based the operation of this system on the control of the NH4 + -N/IC ratio, which was maintained at values of approximately 0.82 g N/g C, close to the values used in the present study.…”
Section: Influence Of the Inlet Ammonium To Inorganic Carbon Ratio (Nsupporting
confidence: 84%
“…Nitrification rates are inhibited when soil pH drops below 6.0 [49,50]. With pH values of the forest soil (4.7) and the agricultural soil (6.5), the original N2O production in the soils potentially were not attributable to microbial nitrification [51][52][53]. It has been observed that fungi produced N2O instead of N2 through codenitrification in the presence of other nitrogen compounds, such as azide, salicylhydroxamic acid, nitrite and ammonium [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Durán et al [68] showed the potential for partial nitrification at low temperature by controlling the aeration frequency, pH value [69] and DO concentration [70] or by adding hydroxylamine to inhibit the activity of NOB.…”
Section: Ph and Temperaturementioning
confidence: 99%